Emergency Powers and Covid-19 in Thailand: Carl Schmitt’s Constitutional Emergency Model Reconsidered - Leelapatana, Rawin (Fakultas Hukum Universitas Muhammadiyah Yogyakarta, 2021)
Carl Schmitt was an anti-liberal conservative jurist during the Weimar Republic in Germany whose position on emergency powers sponsors a hardline form of ‘realism’. To restore peace and order qua the homogeneity of the people in times of crises, he sponsors the role of the sovereign in deciding on an extreme emergency even by transgressing the wordings of a written constitution. However, this article seeks to use the case of the Thai government’s response to Covid-19 through the invocation of emergency powers to expose deficiencies pertaining to the Schmittian model. Rather than calling for the politics of exclusion, the present outbreak of Covid-19 in Thailand reiterates the essence of legality and communitarian and social solidarity.